Register to reply

Forming a formula from a-b=c-d

by khazaymeh
Tags: abcd, forming, formula
Share this thread:
khazaymeh
#1
Mar26-14, 10:10 AM
P: 2
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
Phys.Org News Partner Mathematics news on Phys.org
Professor quantifies how 'one thing leads to another'
Team announces construction of a formal computer-verified proof of the Kepler conjecture
Iranian is first woman to win 'Nobel Prize of maths' (Update)
phinds
#2
Mar26-14, 10:19 AM
PF Gold
phinds's Avatar
P: 6,294
Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
c=a-b+d follows directly from the stated relationship. Where did you get c=a/b*d ???
Mark44
#3
Mar26-14, 10:24 AM
Mentor
P: 21,261
Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
What you got above is correct. To solve for c, add d to both sides of the equation.

I don't know how you got the equation below, but it's incorrect.
Quote Quote by khazaymeh View Post
and c=a/b*d

can I use any other formulas?!!
The equation you started with is very simple, so the only possible differences are how the three terms on the other side are arranged, with a total of six ways.

c = a - b + d
c = a + d - b
c = d + a - b
c = d - b + a
c = -b + a + d
c = -b + d + a

craigi
#4
Mar26-14, 10:24 AM
P: 421
Forming a formula from a-b=c-d

Quote Quote by khazaymeh View Post
Hi, I am beginner in mathematics , I have the following relationship:

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.
I got c=a-b+d
and c=a/b*d

can I use any other formulas?!!
c=a-b+d follows from a-b=c-d

c=a/b*d follows from a/b=c/d

Did you write it down in a way that your -'s look like /'s ?


Register to reply

Related Discussions
Formula forming for Motion in Space General Math 0
Forming a series Calculus & Beyond Homework 1
Forming ln(y)= into y= Calculus & Beyond Homework 1
Forming differential equations..from words to formula Calculus & Beyond Homework 7
Forming DE Differential Equations 4